SISTEM INFORMASI POSYANDU BERBASIS WEB PENGGANTI BUKU KIA DIKELURAHAN KARANGKETUG MENGGUNAKAN METODE PIECES - Dea Pramesti , Frilian; Noval Riswandha, Muhammad (Jurnal Sistem Informasi Aplikasi Teknologi Informasi, 2024)
Teratai Posyandu in Karangketug Village, Pasuruan City, services are carried out manually. Cadres often have difficulties in recording such as data is often lost or duplicate data and it takes quite a long time to make reports. Especially if parents forget to bring the MCH Handbook or tear it, it will affect the recording. Therefore, to overcome the problem, a posyandu information system was built using the waterfall method system development and the analytical method in the form of the PIECES method. The purpose of this research is to develop a system that is still manual so that it becomes a web-based system that can make it easier for posyandu cadres to process data and make it easier for parents to monitor toddler growth more easily.